Koagulopati pada Pasien COVID-19 - Isfandiary, Annisa; Ismandiya; KSS, Nurita Dian; Redjeki, Ike Sri (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
The pathogenesis theory of COVID-19 is still developing. While there are lot of theory coming up, the spotlight mostly reveal on inflamation, coagulopaty, and thrombo-infalamation. We reported an 53 years-old man arrived at the hospital with confirmed COVID-19, severe pneumonia and hypercoagulability state. Patient was referred to Hasan Sadikin Hospital and treated at COVID-19 isolation room, with the used of ventilator for 21 days. Further laboratory test found thromboelastrograph hypercoagulation from elevating level of fibrinogen and thrombocyte. SARS-CoV-2 enter host cells and cause a disruption of both epithelial and endothelial cells together with an alveolar inflammatory cell infiltrate leading to high levels of early response-proinflammatory cytokines. In severe COVID-19 patients, this immune response is excessive and thus described as a systemic “cytokine storm”. It is responsible for endotheliopathy and hypercoagulability state, leading to both systemic and macrothrombosis and microthrombosis. In this case we found hypercoagulation in thromboelastograph with increased D-dimer and fibrinogen, so that the patient was diagnosed with hypercoagulopaty Patient was given therapy of heparin. After heparin therapy patient had an improvement of clinical symptoms and laboratory result.